Remarques Comparatives Sur Le Consonantisme Entre Le Bidiya Et Le Dangaléat - Alio, Khalil (Lingua Posnaniensis, 2010)
The present paper aims at comparing the consonant system of Bidiya and Dangaléat, two languages of the East-Chadic branch spoken in Central Chad Republic. The two languages are neighbours and closely related linguistically speaking. The study is of a comparative nature. It is based on the regular sound correspondences that are intended to bring to light the changes which occurred. These changes are observed first within each language and then between the two languages. It follows that the changes occurring within individual languages and between the two languages are not regular as such, in the sense that there are no rules per se that govern the occurrences of the various sounds. In short, they are not predictable. In conclusion, the significant variation between Dangaléat and Bidiya that deserves further study concerns more the tonal aspect, than the consonantal one.